Signing auditor quality and audit delay: Preliminary evidence - Shukeri, Siti Norwahida; Wan Hussin, Wan Nordin; Aripin, Norhani (American Scientific Publishers, 2015)
The main objective of this paper is to examine the effect of individual audit partner quality on audit delay.The audit partner quality is measured based on whether the signing auditor has been (1) involved in previous misstated financial statements for the period 2011–2013 or (2) reprimanded by the Audit Oversight Board.The findings indicate that the audit partner who frequently restated financial statements in the past or has been censured by the Audit Oversight Board is associated with longer delay in the issuance of audited financial statements.Thus, we provide new evidence that the individual audit partner quality significantly contributes to audit delay.